Asymmetric Organocatalytic Michael/Henry Domino Reactions through Hydrogen‐Bond Activation: Kinetic Access to Indane Scaffolds Bearing cis‐Vicinal Substituents. Issue 33 (2nd July 2013) - Loh, Charles C. J.; Atodiresei, Iuliana; Enders, Dieter
<x xml:space="preserve">Abstract</x> Catalyst directs towards cis! A bifunctional hydrogen‐bond‐catalyzed Michael/Henry domino reaction allows preferential asymmetric access to the kinetic cis‐nitroindanol products with excellent enantioselectivity through a postulated matched transition state (see scheme; H‐Bo = hydrogen bond activation). This high yielding protocol opens up a new strategy to access highly useful enantio‐enriched cis‐aminoindanol‐containing ligands and catalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>